Extraction of Corrosion Inhibitor from Tea Seed Shell and Its Corrosion Inhibition Behavior - MEI Qi - zheng, SHI Ni (Cailiao Baohu)
In order to obtain an environment - friendly and efficient thermal equipment pickling inhibitor, using anhydrous ethanol as the extractant, the effective ingredients in the tea seed shells were extracted by Soxhlet extraction method, and the product could be used as the main components of the thermal equipment pickling inhibitor. The orthogonal test of 4 factors and 3 levels was designed to obtain the extraction conditions of the optimal yield, and the mechanism of the extract as a pickling inhibitor was analyzed. The adsorption isotherm analysis results showed that the adsorption mode on the surface of 20G steel was typical monolayer adsorption. The corrosion inhibition performance of the extract was studied by weight loss method, Tafel polarization and electrochemical AC impedance method. Results showed that under the condition including the acidic medium with the extract concentration of 0.35%, the temperature of (90±1) ℃, tea seed shell extract had good corrosion inhibition performance as a pickling inhibitor for 24 h static coupon in the mixed acid (4% glycolic acid and 1% formic acid) pickling medium. The static corrosion rate of 20G steel was 1.49 g/(m2·h), and the corrosion inhibition rate was 91.38%. Besides, Fe3+ concentration had a great influence on the corrosion inhibition efficiency, and Fe3+ concentration in the pickling solution should be controlled below 300 mg/L. The extract inhibited both the cathode and anode reactions, and belonged to a mixed corrosion inhibitor that mainly controls the anode reaction.